A Rapid Quantification of Serum Free Methionine by HPLC in Relevance to Poultry Industry - NARGISH PARVIN,; TAPAS K. MANDAL,; VIJAYLAXMI SAXENA,; SABYASACHI SARKAR, (International Journal of Pharma and Bio Sciences, 2010)
A sensitive and specific high-performance liquid chromatography (HPLC) method for the separation and quantification of methionine in serum has been developed. After derivatization of serum amino acids with PITC (Phenyl isothiocyanate), a 20 µl sample was loaded on a reversed-phase x-terra MS C18 column (particle size 3.5um, 3.0x150mm). An isocratic program using tetrahydrofuran/methnol/0.1M sodium acetate, pH 7.2 and acetonitrile was used with detection by UV detector. The elution time was 15 minutes. Calibration curves suitable for the analysis of serum were linear (r2 > 0.981) with limits of detection (LOD) was 3.6 pmol/ml. Intraday relative standard deviation and interday were both lower <15.81%and <3.74%. The sensitivity and rapidity of this HPLC method is particularly applicable to provide a more sensitive assessment of protein nutritional status and diet quality of Broiler chicks. This method is applicable to plasma, serum and other complex biological fluids and is suitable for biochemical diagnostic and therapeutic purposes.